Ballistic performance of sandwich tubes - Lim, Bernard Jian Cai. (2010)
Stainless steel tubes were packed with aluminum foams of two different densities, 0.15g/cm3 and 0.41g/cm3. These tubes were penetrated by projectiles (pointed end) to determine their perforation energy. The perforation energy of these tubes was compared to the perforation energy of a coreless stainless steel tube. Having the aluminum foams increased the perforation energy of the tubes relative to the coreless one and the denser the aluminum foam, the greater the increase in perforation energy.